Application Of Integrated Electronic Licensing (Online Single Submission) In Pekalongan City - Aynun Nurmayanti; Widayati Widayati (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2020)
This study aims to determine and analyze licensing arrangements that seek to be integrated electronically (Online Single Submission-OSS) in legislation, the application of OSS in Pekalongan City, and to know and analyze the constraints of OSS implementation in Pekalongan City and its solutions. This study uses a sociological juridical approach with descriptive analysis research specifications. The data used are primary data and secondary data obtained through interviews and literature study. Data analysis method used is qualitative analysis. Furthermore, based on the results of the study it can be concluded: that 1) Government Regulation Number 24 of 2018 On Electronically Integrated Business Licensing seeks to regulate all licenses in Indonesia, but in practice the implementation can only reach a portion of licensing in Indonesia; 2) The issuance of PP 24/2018 does not regulate the transition period of its enactment, the OSS system is not ready, the NSPK has passed the stipulation 15 (fifteen) days since the issuance of the PP, the OSS system has not used Digital Signature, and the weak aspects of supervision, and inefficiency in obtaining permits.Keywords: OSS; Integrated Business Licensing; PP; NSPK.